Tanggung Jawab Pengangkut atas Pengiriman Barang Akibat Overdimension dan Overloading dalam Kegiatan Pengangkutan Darat - Cindy Tatia Amallia; Zahry Vandawati Chymaida (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
In this study will analyze the characteristics of transport vehicles that carry out overdimension and overloading, as well as the responsibility of carriers who carry out overdimension and overloading for the delivery of goods in transportation activities. The approach method used in this study is the Statute Approach and the Conceptual Approach. The existence of carriers that over-dimension and overload can result in negative negative impacts, such as traffic accidents, damage to road infrastructure, the economy, to damage to goods and/or delays in delivery of goods in transportation activities. In this case, the carrier has violated the laws and regulations regarding the permissible load limit. So that the carrier bears the responsibility to provide compensation to the injured party, namely the sender or recipient of the goods.